Female sexual dysfunction among menopausal women. Issue 2 (June 2015) - Mostafa, Taymour; Mostafa, Rashad M.; Hassan, Magdy M.; Nasrallah, Yasser S.; Salman, Wafaa S.; Taymour, Mai
Abstract : Menopause is a natural critical period of every woman's life that is usually associated with physical, behavioral, and psychological changes. This review article aimed to highlight female sexual changes that could take place during such period. A review of the already published articles in this context was carried out using PubMed, Medical Subject Headings (MeSH) database, Excerpta Medica dataBASE, Cochrane Central Register of Controlled Trials, Google Scholar, and Scopus engine until March 2015. The following keywords were used to assess exposure, outcome, and estimates for concerned associations: menopause; sex; female sexual dysfunction; libido; behavior; menopause; postmenopause, humans, and aging. Most studies on this subject correlated hormonal changes during this period with significantly decreased domains of female sexual functions, such as desire, arousal, satisfaction, orgasm, lubrication, and experiencing coital pains. Fortunately, many scientists have taken efforts to alleviate these disorders using emerging treatment methods, topical remedies, and suggested alternative medicament. Significant decreases in female sexual domains are experienced during the postmenopausal period. However, proper counseling, explanations, specific remedies and partner guidance are helpful in overcoming female sexual changes during this period.